Livabilitas Alun-alun Kota Cilegon Berdasarkan Persepsi Pengunjung - Muhammad Dava Noviandhi; Fachmy Sugih Pradifta (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. The city of Cilegon is one of the cities that is nicknamed the industrial city, in line with this nickname, it needs public open spaces that are comfortable and safe for its users to be livable. One of the efforts to increase the liability of public open space in urban areas is a supporting facility to improve the liability conditions of parks. Based on the problems above, the purpose of this study is to identify the Performance and Interests of the Cilegon City Square Facility in Realizing Livability Based on Visitors' Perceptions. The method used in this research is descriptive quantitative. By using the method of importance performance analysis (IPA). Analysis of importance performance analysis shows performance figures with an average of 3.4 while for interests with a figure of 3.88. Based on the results of the analysis, the liability level of Cilegon City Square is 88.43% and 11.57% has not been achieved. Abstrak. Kota Cilegon merupakan salah satu kota yang dijuluki sebagai Kota industri sejalan dengan julukan tersebut diperlukannya ruang terbuka publik yang nyaman serta aman bagi penggunanya supaya livable. Salah satu upaya meningkatkan livabilitas ruang terbuka publik pada kawasan perkotaan, maka diperlukan sebuah fasilitas pendukung untuk meningkatkan kondisi livabilitas pada taman. Berdasarkan permasalahan diatas maka tujuan penelitian ini mengidentifikasi Kinerja dan Kepentingan Fasilitas Alun-Alun Kota Cilegon Dalam Mewujudkan Livabilitas Berdasarkan Persepsi Pengunjung. Metode yang digunakan dalam penelitian ini yaitu kuantitatif deskriptif. Dengan menggunakan metode importance performance analysis (IPA). Analisis importance performance analysis menunjukan angka kinerja dengan rata-rata 3,4 sedangkan untuk kepentingan dengan angka sebesar 3,88. Berdasarkan hasil analisis tingkat livabilitas Alun-Alun Kota Cilegon sebesar 88,43% dan yang belum tecapai 11,57%.